Head up eller North up, vilken av dessa radarpresentationer fungerar bäst vid hög arbetsbelastning? - En simulatorstudie med fokus på radar-arbetet - Helldner, Helene; Knutsson, Johan (My University, 2013)
The development of technical navigation keeps increasing and new navigational instruments are implemented on the ships bridge. All these instruments are a way to get safer navigation, but the question is if the way the equipment is used today is the best? Even older instruments, like the radar, have not been investigated enough. This study is made for clarifying some of these questions. In this study the use of radar is in focus and is comparing the radar modes Head up and North up. To compare these radar modes the BOS (Bridge Operations Simulator) in Chalmers Lindholmen have been used to do simulated runs. In the simulator, the test persons have been driving one simulation in the Head up-mode and one simulation in the North up-mode. When these runs were finished comparisons between the runs have been made to see if one radar mode is better than the other. To complement the data from the simulator runs a web survey was implemented. There were no definitive answers to the question in this study and more research needs to be done. What this study shows is that if one individual is used to one of the radar modes, then this person will keep using that because it feels safest. There is some disinclination to use the radar mode which they are not used to although that radar mode would be more appropriate some times.
Keywords: Transportteknik och logistik; Annan teknik; Transport Systems and Logistics; Other Engineering and Technologies